2019
DOI: 10.1002/ana.25395
|View full text |Cite
|
Sign up to set email alerts
|

The impact of amyloid‐beta and tau on prospective cognitive decline in older individuals

Abstract: Objectives: Amyloid-beta (Aβ) and tau pathologies are commonly observed among clinically normal older individuals at postmortem and can now be detected with in vivo neuroimaging. The association and interaction of these proteinopathies with prospective cognitive decline in normal aging and preclinical Alzheimer's disease (AD) remains to be fully elucidated. Methods: One hundred thirty-seven older individuals (age = 76.3 AE 6.22 years) participating in the Harvard Aging Brain Study underwent Aβ ( 11 C-Pittsburg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
167
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(207 citation statements)
references
References 52 publications
27
167
2
Order By: Relevance
“…The result that CSF tau measures started to change between regional A and cognition in this study is in accordance with the theory that cognitive impairment in AD is caused primarily by tau pathology. This is also in line with other recent studies which show that cognitive impairment is more strongly related to accumulation of tau than to A (Ossenkoppele et al, 2019), and that both tau and A appear necessary for cognitive decline (Sperling et al, 2019). The ordering of the responses coincides with the magnitude of the effect sizes at the time of A-positivity (Table 1), suggesting that initial changes in the responses continue to change in parallel through to the time of A-positivity, without any major differences in acceleration.…”
Section: A Pet and Estimation Of Tfa+supporting
confidence: 93%
“…The result that CSF tau measures started to change between regional A and cognition in this study is in accordance with the theory that cognitive impairment in AD is caused primarily by tau pathology. This is also in line with other recent studies which show that cognitive impairment is more strongly related to accumulation of tau than to A (Ossenkoppele et al, 2019), and that both tau and A appear necessary for cognitive decline (Sperling et al, 2019). The ordering of the responses coincides with the magnitude of the effect sizes at the time of A-positivity (Table 1), suggesting that initial changes in the responses continue to change in parallel through to the time of A-positivity, without any major differences in acceleration.…”
Section: A Pet and Estimation Of Tfa+supporting
confidence: 93%
“…ITG tau PET retention was also associated with lower cross‐sectional attention, and retention in the hippocampus was associated with steeper declines in fluency. Some studies have reported a relationship between tau burden and performance in cognitive domains other than memory [13,46], although these findings may have been driven by the inclusion of clinically impaired individuals, as this relationship is not consistently seen in CN individuals [21].…”
Section: Discussionmentioning
confidence: 99%
“…Results in CN individuals indicate that medial temporal lobe tau PET is associated with lower cross‐sectional episodic memory and steeper retrospective decline in episodic memory adjusting for age, sex, and amyloid burden [18,19]. Other studies have not found associations between regional tau PET and cognition [20], or have shown that tau PET interacts with amyloid to predict greater episodic memory decline only in amyloid+ individuals [21].…”
Section: Introductionmentioning
confidence: 99%
“…To date, most biomarker studies have been adynamic, and so an amyloid "cascade" per se, involving reciprocal synergy between A␤ and tau progression, has yet to be empirically proven in living people. Moreover, existing clinical evidence fails to identify a role of A␤ beyond the initiation of AD pathogenesis, and the nature of its relationship with tau progression has been described only recently as AD symptoms develop and progress (Hanseeuw et al, 2019;Sperling et al, 2019). Possibly due in part to a previous lack of long-term clinical data, the AD cascade has remained an enigmatic target for treatment.…”
Section: Introductionmentioning
confidence: 99%